Relation Between Hormonal Contraception with Menopause - Susanti, Santi; Sulistyoningsih, Hariyani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2021)
Menopause is a process of transition from a productive period heading slowly to the non-productive time due to reduced estrogen and progesterone. There are many factors associated with menopause. Factors contraceptives may affect the occurrence of menopause, which in women who use hormonal contraseption to have compromised menopause compared to those using a non-hormonal contraception. The purpose of this study was to determine the relationship between hormonal contraception and menopause. The research method uses a Systematic Literature Review. The independent variable is hormonal contraception. The dependent variable is Menopause Age. The population is all research journals with the topic of the relationship between hormonal contraception and age menopause. The sample is a journal of research results of the relationship between hormonal contraception and age menopause. Sample inclusion criteria in this study include: 1). Subjects of the study were postmenopausal women, 2). The type of research is case control and cross sectional 4). National and international journals of the10 years last. The results of the study found that hormonal contraception was associated with age at menopause. Suggestions for women postmenopausal to have a healthy lifestyle and have regular the health check posyandu or to health care facilities. Keywords: contraception, hormonal, menopause